193k views
4 votes
Solve the Equation. Show work and explain steps. 2(x +4) +2 = 3(x − 2) +x

User Shali Liu
by
4.5k points

2 Answers

4 votes

Answer:

first step.

Multiply everything in the brackets by the number outside of the brackets.

then; 2x + 8 = 3x - 6

second step.

Collect the like terms, pronumerals on one side and numbers on one side .

2x - 3x = -6 - 8

-x = -14

therefore divide each side by -1 to make it look good then we end up with

x = 14

that's the answer.

User Olayemi
by
5.0k points
3 votes

Answer:

X = 8

Explanation:

A breakdown of the calculation is attached. I hope you find it helpful, thanks.

Solve the Equation. Show work and explain steps. 2(x +4) +2 = 3(x − 2) +x-example-1
User Jeff Musk
by
5.0k points